Asperpyrone A attenuates RANKL‐induced osteoclast formation through inhibiting NFATc1, Ca2+ signalling and oxidative stress. Issue 12 (15th October 2019) - Chen, Xi; Wang, Chao; Qiu, Heng; Yuan, Yu; Chen, Kai; Cao, Zhen; Xiang Tan, Ren; Tickner, Jennifer; Xu, Jiake; Zou, Jun
Abstract: Imbalance of osteoblast and osteoclast in adult leads to a variety of bone‐related diseases, including osteoporosis. Thus, suppressing the activity of osteoclastic bone resorption becomes the main therapeutic strategy for osteoporosis. Asperpyrone A is a natural compound isolated from Aspergillus niger with various biological activities of antitumour, antimicrobial and antioxidant. The present study was designed to investigate the effects of Asperpyrone A on osteoclastogenesis and to explore its underlining mechanism. We found that Asperpyrone A inhibited RANKL‐induced osteoclastogenesis in a dose‐dependent manner when the concentration reached 1 µm, and with no cytotoxicity until the concentration reached to 10 µm. In addition, Asperpyrone A down‐regulated the mRNA and protein expression of NFATc1, c‐fos and V‐ATPase‐d2, as well as the mRNA expression of TRAcP and Ctsk. Furthermore, Asperpyrone A strongly attenuated the RNAKL‐induced intracellular Ca 2+ oscillations and ROS (reactive oxygen species) production in the process of osteoclastogenesis and suppressed the activation of MAPK and NF‐κB signalling pathways. Collectively, Asperpyrone A attenuates RANKL‐induced osteoclast formation via suppressing NFATc1, Ca 2+ signalling and oxidative stress, as well as MAPK and NF‐κB signalling pathways, indicating that this compound may become a potential candidate drug for the prevention or treatment of osteoporosis.